1993
DOI: 10.1046/j.1537-2995.1993.33193142314.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of three types of hepatitis C virus in blood donors: investigation of type‐specific differences in serologic reactivity and rate of alanine aminotransferase abnormalities

Abstract: The serologic reactivity and epidemiology associated with different hepatitis C virus (HCV) variants were investigated in a cohort of 113 anti-HCV-positive donors. In Scotland, HCV type 1 accounted for one-half of all infections; 40 percent of subjects were infected with HCV type 3, and the remainder were infected with type 2. Reactivity with the NS-4-encoded antigens in the first-generation anti-c100 assay was absent in 68 percent of donors infected with types 2 and 3, as compared with 10 percent for those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
150
3
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(164 citation statements)
references
References 32 publications
9
150
3
2
Order By: Relevance
“…Previous work has demonstrated that all six currently defined major genotypes of HCV (Simmonds et al, 1993a;Bukh et al, 1993) can be distinguished on the basis of RFLP analysis of RT-PCR products derived from the 5'NCR (Nakao et al, 1991;McOmish et al, 1993McOmish et al, , 1994Simmonds et al, 1994b). In one previous study, amplified DNA is cleaved with HaeIII-RsaI in one reaction and with MvaI-HinfI in a second, and the virus genotype is deduced by the combination of electropherotypes produced .…”
Section: Predicted Electropherotypes Of Published Hc V 5"ncr Sequencementioning
confidence: 99%
“…Previous work has demonstrated that all six currently defined major genotypes of HCV (Simmonds et al, 1993a;Bukh et al, 1993) can be distinguished on the basis of RFLP analysis of RT-PCR products derived from the 5'NCR (Nakao et al, 1991;McOmish et al, 1993McOmish et al, , 1994Simmonds et al, 1994b). In one previous study, amplified DNA is cleaved with HaeIII-RsaI in one reaction and with MvaI-HinfI in a second, and the virus genotype is deduced by the combination of electropherotypes produced .…”
Section: Predicted Electropherotypes Of Published Hc V 5"ncr Sequencementioning
confidence: 99%
“…Thus, IDUs are considered to be the main risk group for HCV infection and act as a reservoir for this bloodborne virus. Several reports have demonstrated a statistically significant relationship between HCV genotype 3, the injecting drug abuse, and a younger age of infection [45][46][47][48][49]. Moreover, by comparing patients infected with genotype 3 and those infected with other genotypes, numerous groups have revealed an association between this genotype and hepatic steatosis [50][51][52][53][54][55], and a severe histopathological manifestation of CHC which can improve after achieving SVR with the antiviral treatment [56][57][58].…”
Section: Molecular Epidemiology Of Hcv Genetic Diversity and Its Clinmentioning
confidence: 99%
“…To overcome this problem, we used restriction enzyme digestion analysis to detect sequence variations in HCV RNA PCR products (Kato et al, 1991 ;McOmish et al, 1993 ;Nakao et al, 1991). On the basis of the nucleotide sequence data of more than 200 HVR1 cDNA clones derived from serum 1B-2 (Fig.…”
Section: Hpaii Digestion Analysis Of Hvr1 Pcr Productsmentioning
confidence: 99%